?THERMODYNAMIC STUDY OF STRONG ELECTROLYTE IN MIXED SOLVENT SYSTEM FROM CONDUCTANCE AND VISCOSITY METHODS (Biological Sciences - PJSIR, 2000)
The viscosity and ionic conductivity of nickel chloride in 50% (v/v) methanol water mixture at different temperatures have been studied. The conductivity data have been analysed by various equations to evaluate molar conductivity at infinite dilution ",om'Walden constant, equilibrium constant and dissociation constant at different temperatures. The viscosity data have been found to fit in the Jones-Dole equation and the additive character 'B' has been found to depend on the composition of solvent and temperature. Activation parameters have also been evaluated.